(untitled) (International Journal of Engineering and Computer Science, 2018)
MicrostripStrip patch antenna is an important concern in any communication network either it is wired or wireless network. Wireless Communication is an important role in any type of communication. Microstrip patch antenna is generally used because of light weight low cost and easily installed in any type of communication system. Here we are discussed about the different type of antenna for different application and also impedance matching technique by using different type of slotting.. Moreover in microstrip patch antenna which is self- organizing, to enhance the bandwidth as well as gain.